Asphalt penetration type water vapor diffusion coefficient detection method

By constructing a aggregate sample and detection device of composite structure, the penetrating water gas diffusion coefficient of the asphalt oil film layer is solved, and the problem of difficulty in measuring the asphalt water gas diffusion coefficient in the prior art is solved, and effective damage to asphalt pavement is achieved Predict and prevent.

CN119290674APending Publication Date: 2025-01-10HUANGPU BRIDGE OF PEARL RIVER IN GUANGZHOU +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411072190.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-06
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and easily measure the water gas diffusion coefficient of asphalt materials, resulting in the inability to effectively predict and prevent water damage from asphalt pavement.

Method used

Using an asphalt penetration type water and gas diffusion coefficient detection method, the multi-layer structure of the actual asphalt pavement is simulated by constructing a composite structure aggregate sample, including the first and second layer of asphalt oil films, and the multi-layer structure of the actual asphalt pavement is measured by using the detection device. The coefficient is calculated and the penetration water-gas diffusion coefficient of the asphalt oil film layer is determined through formula calculation.

Benefits of technology

Accurate measurement of the water and gas diffusion coefficients of the aggregate layer and the asphalt oil film coated is achieved, simplifying the experimental process, improving the accuracy and efficiency of the measurement, and helping to prevent water damage on the road.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119290674A_ABST
    Figure CN119290674A_ABST
Patent Text Reader

Abstract

The invention provides an asphalt penetration type water vapor diffusion coefficient detection method. The method comprises the following key steps: preparing an aggregate sample coated with an asphalt oil film; measuring the water vapor diffusion coefficient of the test piece sheet by using the detection device through a first formula; respectively measuring the thicknesses of the first asphalt oil film layer, the aggregate layer and the second asphalt oil film layer; and determining the penetration type water vapor diffusion coefficient of the asphalt oil film layer through a second formula. The detection scheme provided by the invention can be implemented under wide environmental conditions, especially for specific temperature ranges and diversified relative humidity gradients, so that a test tool with high flexibility and high adaptability is provided for researchers and engineering quality control experts. Due to the fact that used materials are simple and available and operation procedures are visual and convenient, the method can greatly promote operability and universality of research on the water damage mechanism of the asphalt mixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road construction engineering, in particular to an asphalt penetration type water vapor diffusion coefficient detection method. Background Art

[0002] One of the root causes of the frequent cracking, surface porosity, and even potholes encountered on highway asphalt pavements can be attributed to the cumulative effects of water damage, a problem that has become a primary obstacle to pavement stability and durability. Existing scientific research clearly indicates that the water vapor diffusion capacity of asphalt materials is closely related to their susceptibility to water damage. Specifically, the permeation and migration of water molecules within the asphalt mixture is not only a silent erosion process, but also an invisible force that gradually weakens the material's structural integrity. This process involves water vapor carrying moisture deep into the asphalt mixture and at the asphalt-aggregate interface, resulting in a significant decrease in the intermolecular cohesion within the asphalt film and the adhesion between the asphalt and aggregate.

[0003] As these two key bonding forces weaken, the asphalt film itself becomes susceptible to internal separation and failure, while the adhesion interface between the asphalt and aggregate becomes fragile, laying the groundwork for subsequent physical damage. Especially under repeated vehicle loads, these initial microscopic damages gradually evolve into macroscopically visible pavement defects, accelerating the degradation of the entire pavement system. Therefore, in-depth research and quantification of the water vapor diffusion coefficient of asphalt is crucial for predicting, preventing, and even managing water damage to asphalt pavements.

[0004] Asphalt is a key component of asphalt mixtures. However, due to its fluidity and tendency to deform under gravity, its penetrating water vapor diffusion coefficient cannot be directly measured experimentally. Therefore, a convenient and accurate test method for calculating the water vapor diffusion coefficient of asphalt under multiple humidity gradients is urgently needed to provide a theoretical basis for studying the mechanisms of water damage in asphalt mixtures. Therefore, how to quickly and easily measure the water vapor diffusion coefficient of asphalt is an urgent problem to be solved.

[0005] In view of this, it is necessary to provide an asphalt penetration type water vapor diffusion coefficient detection method to solve the problem of how to quickly and easily measure the water vapor diffusion coefficient of asphalt in the prior art. Summary of the Invention

[0006] The purpose of the present invention is to address the shortcomings of the existing technology and provide a method for detecting the penetrating water vapor diffusion coefficient of asphalt. The method accurately measures the water vapor diffusion coefficients of the aggregate main layer and the aggregate sample coated with asphalt oil film, and measures the thickness of each layer. The penetrating water vapor diffusion coefficient of the asphalt oil film layer can be determined efficiently and accurately through a simple formula. The experimental materials are simple and easy to obtain, and the test method is simple and easy to operate, which helps to prevent water damage on the road.

[0007] This invention is achieved through the following technical solution: a method for measuring the water vapor diffusion coefficient of asphalt through penetration. Its unique feature is a systematic process specifically designed to evaluate the water vapor diffusion characteristics of specially treated aggregate samples. The core component of this process is a composite aggregate sample with a unique layered structure: a first asphalt film, a central aggregate layer, and a second asphalt film, from the surface to the interior, accurately simulating the multi-layered structure of an actual asphalt pavement.

[0008] The water vapor diffusion coefficient of the test piece slice is measured by the detection device using the following first formula: wherein the test piece slice includes an aggregate sample not coated with an asphalt oil film and an aggregate sample coated with an asphalt oil film.

[0009]

[0010] Among them, D x is the water vapor diffusion coefficient of the specimen sheet, A is the effective diffusion area, is the water vapor permeability detected in the detection device, R is the universal gas constant; T is the test Kelvin temperature; is the relative molecular mass of water; L is the average thickness of the specimen slice; P1 and P0 are the water vapor partial pressures on both sides of the specimen slice.

[0011] When the temperature remains unchanged, the water vapor partial pressure is proportional to the relative humidity. The thicknesses of the first asphalt oil film layer, the middle aggregate main layer and the second asphalt oil film layer are measured respectively, and the penetrating water vapor diffusion coefficient of the asphalt oil film layer is determined by the following second formula.

[0012] The penetrating water vapor diffusion coefficient of the asphalt oil film layer is determined by the following second formula:

[0013]

[0014] in, is the penetration water vapor diffusion coefficient of the asphalt oil film layer, is the water vapor diffusion coefficient of the aggregate sample coated with asphalt oil film, is the water vapor diffusion coefficient of the aggregate sample not coated with asphalt oil film, h1 is the thickness of the first asphalt oil film layer, h2 is the thickness of the aggregate layer, and h3 is the thickness of the second asphalt oil film layer.

[0015] Two types of aggregate samples were selected: one coated with asphalt oil film and the other not coated with asphalt oil film.

[0016] The aggregate sample not coated with asphalt oil film is cleaned, evaporated, and polished into flat particles with a smooth surface. At a heating temperature, asphalt is wrapped on the surface of the flat particles with a smooth surface. After cooling to room temperature, the thickness of the asphalt oil film at different positions is measured to ensure that the thickness at each position is consistent.

[0017] The preparation of the detection device includes:

[0018] First, a glass container of consistent specifications was used as the matrix, and a saturated sodium chloride solution was poured into it to maintain a constant relative humidity inside the container and ensure the stability and controllability of the experimental conditions.

[0019] Next, the sealing structure is constructed. The top edge of the container is tightly fitted with a circular silicone sheet to enhance sealing performance. The container's opening is connected to a sealing groove at the bottom edge of the annular silicone sheet. This groove is equipped with an elastic sealing rubber ring that precisely matches the opening size of the plastic container, achieving a seamless closure and ensuring the airtightness and humidity control of the internal environment.

[0020] Next, the specimen is positioned and secured. An annular collar, slightly larger in diameter than the specimen sheet, is mounted on top of the circular silicone plate. The specimen sheet is securely placed within this collar, and the tiny gap between the two is sealed using grouting technology. This not only secures the specimen in place but also further improves the sealing of the entire device and the accuracy of the test.

[0021] The last step is to measure the mass. After completing the above assembly, the initial mass of the entire detection device is accurately measured. Here, a cantilever pressure sensor is mainly used to accurately measure the experimental device. The initial mass value obtained will be displayed on the central pressure display screen. This data is crucial for the analysis of subsequent experimental results and can be used as a basic reference value for evaluating the mass change of the specimen under specific test conditions.

[0022] Through this series of carefully designed and rigorously executed preparation processes, the reliability of the detection device and the accuracy of the test results are ensured, providing solid technical support for in-depth research.

[0023] The water vapor transmission rate detection process includes:

[0024] The detection device is placed on the cantilever pressure sensor, and then placed in an environmental box with constant temperature and humidity, so that the inside and outside of the detection device reach a specific test temperature and different relative humidity gradient environments. The change in mass M of the detection device is weighed and recorded at predetermined time intervals. i , according to the initial mass M0 relative to the change mass M i The water vapor permeability is determined by the curve of change over time.

[0025]

[0026] As a preferred embodiment of the present invention, the water vapor concentration conditions of the aggregate samples coated with asphalt oil film are measured respectively, wherein the water vapor concentration conditions include a first water vapor concentration condition of the first asphalt oil film layer away from one end of the aggregate layer, a second water vapor concentration condition between the first asphalt oil film layer and the aggregate layer, a third water vapor concentration condition between the aggregate layer and the second asphalt oil film layer, and a fourth water vapor concentration condition of the second asphalt oil film layer away from one end of the aggregate layer.

[0027] Finally, the penetrating water vapor diffusion coefficient of the asphalt oil film layer is determined according to the water vapor concentration condition, the thickness of the first asphalt oil film layer, the thickness of the aggregate layer, and the thickness of the second asphalt oil film layer.

[0028] As a preferred embodiment of the present invention, the penetrating water vapor diffusion coefficient of the asphalt oil film layer is determined by the following third formula.

[0029]

[0030] Among them, C1 is the first water vapor concentration condition, C2 is the second water vapor concentration condition, C3 is the third water vapor concentration condition, C4 is the fourth water vapor concentration condition, h1 is the thickness of the first asphalt oil film layer, h2 is the thickness of the aggregate layer, h3 is the thickness of the second asphalt oil film layer, and J is the diffusion flux of the aggregate sample coated with the asphalt oil film.

[0031] As a preferred embodiment of the present invention, the diffusion flux of the aggregate sample coated with the asphalt oil film is determined by the following fourth formula.

[0032]

[0033] in, is the water vapor diffusion coefficient of the aggregate sample not coated with asphalt oil film, C2 is the second water vapor concentration condition, C3 is the third water vapor concentration condition, and h2 is the thickness of the aggregate layer.

[0034] In summary, the present invention has the following beneficial effects:

[0035] On the one hand, an aggregate sample coated with an asphalt oil film is prepared to effectively construct an aggregate sample comprising a first asphalt oil film layer, an aggregate layer and a second asphalt oil film layer; and then a detection device is used to measure the water vapor diffusion coefficient of the aggregate sample not coated with the asphalt oil film (equivalent to the aggregate layer) and the water vapor diffusion coefficient of the aggregate sample coated with the asphalt oil film, so as to effectively reflect the changes in the water vapor diffusion coefficient of the aggregate sample caused by the asphalt oil film.

[0036] On the other hand, a sealing groove is set at the place where the lower part of the annular silicone plate contacts the glass container. The built-in sealing rubber ring and the annular ring for loading the specimen are tightly sealed using sealing slurry technology. During the experiment, water vapor can only pass through the specimen upward and will not overflow to other places. This ensures the accuracy of the test to a great extent, reduces test errors, and solves the pain points of traditional test equipment.

[0037] Moreover, the test device uses a cantilever pressure sensor to measure the real-time weight of the device, which is conducive to the statistics of test data and the analysis of test results. At the same time, no manual operation is required for measurement, which ensures the continuity of the test and greatly reduces the errors caused by human operation.

[0038] In summary, the present invention accurately measures the water vapor diffusion coefficient of the aggregate layer and the aggregate sample coated with asphalt oil film, and measures the thickness of each layer. The penetrating water vapor diffusion coefficient of the asphalt oil film layer can be efficiently and accurately determined through a simple formula. The experimental materials are simple and easy to obtain, and the test method is simple and easy to operate, which helps to prevent water damage on the road. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 A schematic diagram of the test device provided by the present invention;

[0040] Figure 2 A schematic flow chart of the asphalt penetration type water vapor diffusion coefficient detection method provided by the present invention;

[0041] Figure 3 Schematic diagram of penetrating water vapor diffusion of asphalt oil film coated aggregate provided by the present invention;

[0042] Figure 4 A schematic diagram of the process for preparing an aggregate sample coated with an asphalt oil film provided by the present invention;

[0043] Figure 5 A schematic diagram of a process for measuring the water vapor diffusion coefficient of a test piece sheet provided by the present invention;

[0044] Figure 6 A schematic diagram of a process for determining water vapor permeability provided by the present invention;

[0045] Figure 7 This is a schematic flow chart of the asphalt penetration type water vapor diffusion coefficient detection method provided by the present invention. DETAILED DESCRIPTION

[0046] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0047] In the description of the present invention, it should be noted that the terms "vertical," "upper," "lower," and "horizontal," etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings and are intended solely to facilitate the description of the present invention and simplify the description. They do not indicate or imply that the devices or components referred to must have, be constructed, or operate in a specific orientation, and therefore should not be construed as limitations on the present invention. Furthermore, the terms "first," "second," "third," and "fourth" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.

[0048] It should also be noted that, in the description of the present invention, unless otherwise expressly specified or limited, the terms "disposed," "installed," "connected," and "connected" should be understood in a broad sense. For example, they may refer to fixed connections, detachable connections, or integral connections; they may refer to mechanical connections or electrical connections; they may refer to direct connections or connections through an intermediate medium; and they may refer to internal communication between two components. Those skilled in the art will understand the specific meanings of the above terms in the present invention based on specific circumstances.

[0049] Example 1

[0050] This example discloses a technical solution for determining the water vapor diffusion coefficient of asphalt permeability. The technical details are as follows: Figure 1 To further elaborate, Figure 2 A flowchart of the technical method is presented, which comprehensively summarizes the entire detection process from step S1 to step S4.

[0051] In the initial stage S1, the aggregate sample needs to be prepared. This preparation process specifically involves tightly wrapping the main layer of aggregate between two layers of asphalt oil film - both the bottom layer and the overlying layer are coated with asphalt oil film, thus forming a three-layer structural system as a whole.

[0052] The next key step, S2, involved measuring the water vapor diffusion coefficient of the specimen slice using a detection device and accurately quantifying its water vapor diffusion capacity using the first formula. Two types of specimens were selected: one was pristine aggregate sample, uncoated with asphalt film, serving as a baseline control; the other was aggregate sample that had undergone the aforementioned special treatment, namely, coated with a double layer of asphalt film. This comparative analysis not only visually reveals the changes in the water vapor diffusion properties of the aggregate before and after the addition of the asphalt film, but also provides a deeper understanding of the regulatory mechanism of the asphalt coating on water vapor management in the aggregate microenvironment.

[0053]

[0054] Among them, D x is the water vapor diffusion coefficient of the specimen sheet, A is the effective diffusion area, is the water vapor permeability detected in the detection device, R is the universal gas constant; T is the test Kelvin temperature; is the relative molecular mass of water; L is the average thickness of the specimen sheet; P1 and P0 are the water vapor partial pressures on both sides of the specimen sheet. When the temperature remains unchanged, the water vapor partial pressure is proportional to the relative humidity.

[0055] In step S3, the thicknesses of the first asphalt oil film layer, the middle aggregate main body layer, and the second asphalt oil film layer are measured respectively.

[0056] In step S4, the penetrating water vapor diffusion coefficient of the asphalt oil film layer is determined by the following second formula.

[0057]

[0058] in, is the penetration water vapor diffusion coefficient of the asphalt oil film layer, is the water vapor diffusion coefficient of the aggregate sample coated with asphalt oil film, is the water vapor diffusion coefficient of the aggregate sample without asphalt oil film, h1 is the thickness of the first asphalt oil film layer, h2 is the thickness of the aggregate layer, and h3 is the thickness of the second asphalt oil film layer.

[0059] In this example, we first constructed a multilayered model by coating aggregate samples with an asphalt film. This model consists of a bottom first asphalt film layer, a middle aggregate layer, and a top second asphalt film layer. High-precision testing equipment was then used to measure the water vapor diffusion coefficients of two groups of samples: one group of untreated aggregate samples and the other group of treated aggregate samples. This effectively demonstrates the potential modification of the asphalt film coating on the water vapor diffusion properties of the aggregate, providing key data support for subsequent analysis.

[0060] On this basis, we further accurately measured the thickness of the above three layers - the first asphalt oil film, the main aggregate layer and the last asphalt oil film.

[0061] In the final stage, the penetrating water vapor diffusion coefficient of the asphalt oil film layer is quickly determined based on the previously measured water vapor diffusion coefficient and the thickness of each layer.

[0062] Figure 3 This is a schematic diagram of penetrating water vapor diffusion through asphalt-coated aggregate provided by the present invention. It should be noted that, under the influence of the relative humidity gradient, water vapor vertically penetrates the three layers of material, maintaining the diffusion flux J in any horizontal direction within the composite material. Furthermore, the top and bottom cross-sectional areas are identical to those of each layer. According to Fick's first law, the effective diffusion coefficients of asphalt and aggregate satisfy the following relationship:

[0063]

[0064] In the above formula, J represents the diffusion flux, the unit is g / mm 2 h; h1 and h3 represent the asphalt film thickness (the first asphalt film layer and the second asphalt film layer), in mm; h2 represents the aggregate thickness (aggregate layer), in mm; C1, C2, C3, and C4 represent the water vapor concentration conditions, in g / mm 3 ; Indicates the asphalt oil film penetration water vapor diffusion coefficient, unit is mm 2 / h; represents the aggregate penetration water vapor diffusion coefficient, unit is mm 2 / h.

[0065] If the sample is regarded as a whole, the effective diffusion coefficient measured experimentally can be expressed as:

[0066]

[0067] From the above formula, we can know that the effective diffusion coefficient and the diffusion coefficient of aggregate can be directly tested through the experiment. At the same time, the aggregate thickness h2 and asphalt thickness h can be measured. a =h1+h3. Therefore, formula (3) can be converted into formula (5), which can be used to calculate the penetration type water vapor diffusion coefficient of the asphalt film, and then formula (2) can be obtained.

[0068] Preferably, Figure 4 This is a schematic diagram of a process for preparing an aggregate sample coated with an asphalt oil film provided by the present invention. The above step S1 includes steps S11 to S13, wherein:

[0069] In step S11, an aggregate sample not coated with an asphalt oil film is selected;

[0070] In step S12, the aggregate sample not coated with the asphalt oil film is cleaned, evaporated, and polished into flat particles with a smooth surface;

[0071] In step S13, at a heating temperature, asphalt is coated on the surface of flat particles with a smooth surface. After cooling to room temperature, the thickness of the asphalt film at different positions is measured to ensure that the thickness at each position is consistent.

[0072] At the same time, the sample needs to be cleaned, evaporated, and polished to ensure that the aggregate surface is smooth and polished to a certain degree, creating ideal conditions for uniform asphalt film application. Furthermore, the thickness distribution of the asphalt film on the aggregate sample must be monitored at multiple locations to ensure consistency and uniformity of the film layer. This practice is crucial for the subsequent accurate evaluation of the water vapor diffusion coefficient, effectively eliminating errors that may be introduced by local thickness variations and improving the reliability of the experimental data.

[0073] In one specific implementation, the preparation process involves selecting ten aggregate particles with a particle size exceeding 13.2 mm. The particles are first cleaned with distilled water and then placed in a 170°C oven for four hours to ensure thorough drying. To reduce external interference, the particles are file-finished to a smooth surface, and a caliper is used to confirm uniform thickness. Next, the selected asphalt is heated to the recommended temperature range of 160-170°C and the particles are impregnated with tweezers. After cooling, the asphalt coating is checked to ensure a consistent thickness, ensuring uniform coverage of the aggregate surface.

[0074] Preferably, Figure 5 This is a schematic diagram of a process for measuring the water vapor diffusion coefficient of a test piece provided by the present invention. The preparation of the detection device in step S2 includes steps S21 to S24, wherein:

[0075] In step S21, a glass container of uniform specifications is used, and a saturated sodium chloride solution is injected into the glass container to control the relative humidity inside the glass container to be stable;

[0076] In step S22, the opening of the glass container is placed into the sealing groove at the bottom of the circular silicone plate and sealed with a sealing rubber ring;

[0077] In step S23, the test piece is placed in the annular collar, and the gap between the annular collar and the test piece is sealed with grout;

[0078] In step S24 , the test device is placed stably on the cantilever pressure sensor, and the initial mass M0 of the device is detected.

[0079] Thus, a detection device with good sealing performance is obtained through the above steps, so as to effectively measure the mass change and ensure the rapid measurement of the water vapor diffusion coefficient.

[0080] The effective diffusion area is the inner ring area of ​​the annular silicone plate. Therefore, the effective diffusion area can be effectively measured based on the inner ring area of ​​the annular silicone plate.

[0081] Preferably, Figure 6 This is a flow chart of determining the water vapor permeability provided by the present invention. The process of determining the water vapor permeability in step S2 includes steps S25 to S27, wherein:

[0082] In step S25, the detection device and the cantilever pressure sensor are placed in an environmental chamber with a constant temperature and humidity, so that the inside and outside of the detection device reach a specific test temperature and different relative humidity gradient environments;

[0083] In step S26, the change in mass M of the detection device is weighed and recorded at every predetermined time period. t ;

[0084] In step S27, the initial mass M0 is calculated relative to the change mass M t The water vapor transmission rate is determined by the curve of change over time.

[0085] Therefore, the excellent sealing performance of the detection device is utilized to monitor the changes in water vapor permeability according to the changes in mass, so as to quickly and accurately evaluate the water vapor transmission rate.

[0086] Preferably, Figure 7 This is a flow chart of the asphalt penetrating water vapor diffusion coefficient detection method provided by the present invention. The asphalt penetrating water vapor diffusion coefficient detection method further includes steps S5 to S6, wherein:

[0087] In step S5, the water vapor concentration conditions of the aggregate samples coated with the asphalt oil film are measured respectively, wherein the water vapor concentration conditions include a first water vapor concentration condition at an end of the first asphalt oil film layer away from the aggregate layer, a second water vapor concentration condition between the first asphalt oil film layer and the aggregate layer, a third water vapor concentration condition between the aggregate layer and the second asphalt oil film layer, and a fourth water vapor concentration condition at an end of the second asphalt oil film layer away from the aggregate layer;

[0088] In step S6, the penetrating water vapor diffusion coefficient of the asphalt oil film layer is determined according to the water vapor concentration condition and the thicknesses of the first asphalt oil film layer, the aggregate layer, and the second asphalt oil film layer.

[0089] Therefore, by using the aggregate samples coated with asphalt oil film, observing the changes in the water vapor concentration inside them, and considering the thickness of each layer (first asphalt film, aggregate layer, and last asphalt film), the water vapor permeability performance can be effectively evaluated.

[0090] Specifically, the penetration-type water vapor diffusion coefficient of the asphalt oil film layer is determined by the following third formula.

[0091]

[0092] Among them, C1 is the first water vapor concentration condition, C2 is the second water vapor concentration condition, C3 is the third water vapor concentration condition, C4 is the fourth water vapor concentration condition, h1 is the thickness of the first asphalt oil film layer, h2 is the thickness of the aggregate layer, h3 is the thickness of the second asphalt oil film layer, and J is the diffusion flux of the aggregate sample coated with the asphalt oil film.

[0093] Specifically, the diffusion flux of the aggregate sample coated with the asphalt oil film is determined by the following fourth formula.

[0094]

[0095] in, is the water vapor diffusion coefficient of the aggregate sample without asphalt oil film, C2 is the second water vapor concentration condition, C3 is the third water vapor concentration condition, and h2 is the thickness of the aggregate layer.

[0096] In another specific embodiment of the present invention, limestone, a typical road aggregate, is used for the test.

[0097] The selected aggregate particle size was no less than 12.6 mm. The particles were cleaned with distilled water and then placed in an oven at 170°C for 4 hours to thoroughly remove internal moisture and ensure complete evaporation of the moisture within the aggregate. To minimize the influence of variables such as surface texture on the experimental structure, the particles were filed to a smooth, flat surface. The thickness was then measured at multiple points with a micrometer to ensure uniformity, ensuring that the flat particles were of approximately the same thickness.

[0098] Two parallel tests were conducted for each type of aggregate, so a total of six flat aggregates were required for the test. The thickness of the aggregates in the three test groups for the three aggregate types is listed in Table 1.

[0099] Table 1

[0100]

[0101] Furthermore, 70# base asphalt and SBS modified asphalt were used to coat the aggregate particles. These two asphalts were stored in aluminum containers and heated to 165°C and 175°C, respectively. Aggregate particles were melted into the 70# base asphalt and SBS modified asphalt using tweezers. After cooling to room temperature, the thickness of the asphalt film was measured at different locations to ensure that the film was uniform across the aggregate particles. For each aggregate type, the first group of particles served as control samples and were uncoated with asphalt; the second group was coated with 70# asphalt; and the third group was coated with SBS modified asphalt. The thickness of all specimens is shown in Table 2.

[0102] Table 2

[0103]

[0104] Furthermore, distilled water was stored in a glass container, and the specimen was placed in an annular collar. The gap between the collar and the specimen was sealed with grouting. The relative humidity (RH1) within the glass container was maintained at 100%. The test apparatus was then placed in an environmental chamber with a constant temperature and humidity setting of 65% ± 3% (set to RH2) and a temperature of 25°C ± 0.5°C. The test sample was subjected to water vapor diffusion under the influence of relative humidity differences (65% ± 3% to 100%).

[0105] The preparation of the detection device includes:

[0106] The first step is to use a glass container of uniform specifications and inject a saturated sodium chloride solution into it that can maintain a constant relative humidity in the internal environment of the container. The top edge of the container is tightly fitted with a circular silicone plate, and the opening end of the container is connected to the sealing groove set at the bottom edge of the circular silicone plate to accurately match the opening size of the glass container and achieve sealing.

[0107] The second step is to install an annular collar with a diameter slightly larger than the specimen sheet on top of the circular silicone plate. The specimen is placed in the collar, and the small gap between the two is filled and sealed using grouting technology.

[0108] After completing the above assembly, the initial mass of the entire detection device is accurately measured. Here, a cantilever pressure sensor is mainly used to accurately measure the experimental device. The obtained initial mass value will be displayed on the central pressure display.

[0109] The water vapor transmission rate testing process includes:

[0110] The first step is to place the detection device on the cantilever pressure sensor, and then place the whole device in an environmental chamber with constant temperature and humidity, so that the inside and outside of the detection device reach a specific test temperature and different relative humidity gradient environments. At predetermined time intervals, the change in mass M of the detection device is weighed and recorded. i , according to the initial mass M0 relative to the change mass M i The water vapor permeability is determined by the curve of change over time.

[0111] The second step is to measure the water vapor concentration conditions of the aggregate samples coated with asphalt oil film respectively, wherein the water vapor concentration conditions include the first water vapor concentration condition of the first asphalt oil film layer away from one end of the aggregate layer, the second water vapor concentration condition between the first asphalt oil film layer and the aggregate layer, the third water vapor concentration condition between the aggregate layer and the second asphalt oil film layer, and the fourth water vapor concentration condition of the second asphalt oil film layer away from one end of the aggregate layer.

[0112] The third step is to determine the penetrating water vapor diffusion coefficient of the asphalt oil film layer according to the water vapor concentration condition, the thickness of the first asphalt oil film layer, the thickness of the aggregate layer and the thickness of the second asphalt oil film layer.

[0113] The water vapor diffusion coefficient of the sample corresponding to each specific test temperature and relative humidity gradient condition can be calculated by the above first formula. x is the water vapor diffusion coefficient of the specimen sheet, A is the effective diffusion area, is the water vapor permeability detected in the detection device, R is the universal gas constant; T is the test Kelvin temperature; is the relative molecular mass of water; L is the average thickness of the specimen; P1 and P0 are the water vapor partial pressures on both sides of the specimen, which are proportional to the relative humidity when the temperature is constant. P sat is the saturated vapor pressure at a certain temperature.

[0114] It should be noted that the assembled test device is placed in a constant temperature and humidity chamber. Under the action of the △RH formed between RH1 and RH2, water vapor is driven to diffuse from the container through the sample into the constant temperature and humidity chamber. A high-precision balance with a maximum range of 320g and an accuracy of 0.1mg is used to measure the initial mass M of each test device, as well as the mass M of the test device every 48 hours during the test. The mass loss of the test device during the test is ΔM=M0-M, which is the mass of water vapor diffused through the test sample. The water vapor diffusion coefficient and diffusion flux of the asphalt mixture specimen at the test temperature and different relative humidity gradients can be calculated based on the measured mass loss rate of water in the test device and the above formula. Taking limestone as an example, its water vapor diffusion coefficient and diffusion flux are shown in Table 3. At the same time, the water vapor diffusion coefficient of the asphalt oil film calculated according to the above formula is shown in Table 4. In Table 4, the aggregate diffusion coefficient is the water vapor diffusion coefficient of the aggregate sample not coated with asphalt oil film (aggregate layer), the effective diffusion coefficient is the water vapor diffusion coefficient of the aggregate sample coated with asphalt oil film, and the asphalt diffusion coefficient is the penetrating water vapor diffusion coefficient of the asphalt oil film layer.

[0115] Calculations show that the diffusion coefficient of aggregates significantly decreases after the asphalt film is applied, highlighting the film's effectiveness in inhibiting water penetration. The experiments demonstrate that the barrier effect of the asphalt film is a key factor in understanding the water vapor transport mechanisms within asphalt mixtures. The nearly tenfold decrease in diffusion coefficient caused by asphalt coating suggests that water vapor migration within the asphalt mixture structure prefers to utilize the rich pore network within the material rather than directly permeating the asphalt film.

[0116] The test results show that the average penetration water vapor diffusion coefficient of 70# matrix asphalt is 1.98mm 2 / h, the average penetrating water vapor diffusion coefficient of SBS modified asphalt is 2.44mm 2 The calculation results show that the penetrating water vapor diffusion coefficient of aggregate is about 200 times that of asphalt, which proves that the asphalt film can significantly hinder the diffusion of water vapor from the outside into the aggregate.

[0117] Table 3

[0118]

[0119] Table 4

[0120]

[0121] This invention focuses on cutting-edge technological improvements in road construction projects, and is particularly committed to creating an innovative asphalt-penetrating water vapor diffusion coefficient detection technology. This technology is deeply involved in solving the core link of pavement water damage problems. Through precise detection means and scientific analysis methods, this invention has opened up a new way to improve the long-term stability and weather resistance of road infrastructure.

[0122] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A method for detecting water vapor diffusion coefficient of asphalt penetration type, comprising a composite aggregate sample, the sample is uniquely arranged in layers, from the surface to the inside, respectively comprising a first asphalt oil film layer, a middle aggregate main layer and a second asphalt oil film layer, accurately simulating the multi-layer structure of an actual asphalt pavement; characterized in that: The water vapor diffusion coefficient of the test piece slice is measured by using the detection device through the following first formula; wherein the test piece slice includes an aggregate sample not coated with an asphalt oil film and an aggregate sample coated with an asphalt oil film; Among them, D x is the water vapor diffusion coefficient of the specimen sheet, A is the effective diffusion area, is the water vapor permeability detected in the detection device, R is the universal gas constant; T is the test Kelvin temperature; is the relative molecular mass of water; L is the average thickness of the sample sheet; P1 and P0 are the water vapor partial pressures on both sides of the sample sheet; Under the condition of constant temperature, the water vapor partial pressure is proportional to the relative humidity. The thickness of the first asphalt oil film layer, the middle aggregate main layer and the second asphalt oil film layer are measured respectively, and the penetration type water vapor diffusion coefficient of the asphalt oil film layer is determined by the following second formula; in, is the penetration type water vapor diffusion coefficient of the asphalt oil film layer, is the water vapor diffusion coefficient of the aggregate sample coated with asphalt oil film, is the water vapor diffusion coefficient of the aggregate sample not coated with asphalt oil film, h1 is the thickness of the first asphalt oil film layer, h2 is the thickness of the aggregate main body layer, and h3 is the thickness of the second asphalt oil film layer; Two types of aggregate samples, one coated with asphalt oil film and the other not coated with asphalt oil film, were selected; The aggregate sample not coated with asphalt oil film is cleaned, evaporated, and polished into flat particles with smooth surfaces. At a heating temperature, asphalt is coated on the surface of the flat particles with smooth surfaces. After cooling to room temperature, the thickness of the asphalt oil film at different positions is measured to ensure that the thickness at each position is consistent. The water vapor transmission rate detection process includes: The detection device is placed on the cantilever pressure sensor, and then placed in an environmental box with constant temperature and humidity, so that the inside and outside of the detection device reach a specific test temperature and different relative humidity gradient environments. The change in mass M of the detection device is weighed and recorded at predetermined time intervals. i , according to the initial mass M0 relative to the change mass M i The water vapor permeability is determined by the time-varying curve.

2. The asphalt penetration type water vapor diffusion coefficient detection method according to claim 1, characterized in that: The preparation of the detection device comprises: Step S1, using a glass container of consistent specifications as a substrate, and pouring a saturated sodium chloride solution into the container to maintain a constant relative humidity inside the container to ensure the stability and controllability of the experimental conditions; Step S2, constructing a sealing structure, wherein the top edge of the glass container is tightly fitted with a circular silicone plate to enhance the sealing performance; the opening end of the glass container is connected to a sealing groove provided at the lower edge of the circular silicone plate, and an elastic sealing rubber ring is arranged in the sealing groove to accurately match the opening size of the plastic container to achieve gapless closure, thereby ensuring the airtightness and humidity control of the internal environment; Step S3, specimen placement and fixation: an annular ring with a diameter slightly larger than the specimen slice is installed on the upper part of the annular silicone plate; the specimen slice is securely placed in the annular ring, and the small gap between the two is filled and sealed by grouting technology to fix the specimen position; Step S4, mass determination. After completing the above assembly, the initial mass M0 of the entire detection device is accurately measured. The cantilever pressure sensor is used to accurately measure the experimental device. The obtained initial mass value will be displayed on the central pressure display screen as a basic reference value for evaluating the mass change of the test piece under specific test conditions.

3. The asphalt penetration type water vapor diffusion coefficient detection method according to claim 1, characterized in that: The effective diffusion area is the inner ring area of ​​the annular silica gel plate.

4. The asphalt penetration type water vapor diffusion coefficient detection method according to claim 1, characterized in that: The water vapor concentration conditions of the aggregate samples coated with the asphalt oil film are measured respectively; the water vapor concentration conditions include a first water vapor concentration condition of the first asphalt oil film layer away from the aggregate main body layer, a second water vapor concentration condition between the first asphalt oil film layer and the aggregate main body layer, a third water vapor concentration condition between the aggregate main body layer and the second asphalt oil film layer, and a fourth water vapor concentration condition of the second asphalt oil film layer away from the aggregate main body layer; Finally, the penetrating water vapor diffusion coefficient of the asphalt oil film layer is determined according to the water vapor concentration condition, the thickness of the first asphalt oil film layer, the thickness of the aggregate main layer and the thickness of the second asphalt oil film layer.

5. The asphalt penetration type water vapor diffusion coefficient detection method according to claim 4, characterized in that: The penetration type water vapor diffusion coefficient of the asphalt oil film layer is determined by the following third formula; Among them, C1 is the first water vapor concentration condition, C2 is the second water vapor concentration condition, C3 is the third water vapor concentration condition, C4 is the fourth water vapor concentration condition, h1 is the thickness of the first asphalt oil film layer, h2 is the thickness of the aggregate main layer, h3 is the thickness of the second asphalt oil film layer, and is the diffusion flux of the aggregate sample coated with asphalt oil film.

6. The asphalt penetration type water vapor diffusion coefficient detection method according to claim 1, characterized in that: The diffusion flux of the aggregate sample coated with the asphalt oil film is determined by the following fourth formula; in, is the water vapor diffusion coefficient of the aggregate sample not coated with asphalt oil film, C2 is the second water vapor concentration condition, C3 is the third water vapor concentration condition, and h2 is the thickness of the aggregate main layer.